PERTANGGUNGJAWABAN HUKUM PERUSAHAAN PERS DALAM PUBLIKASI BERITA YANG BERMUATAN CONTEMPT OF COURT - Kristianus Jimy Pratama (Faculty of Law - Tarumanagara University, 2020)
Based on General Section item (4) of General Section item (4) of the Explanation of Law Number 14 of 1985 concerning the Supreme Court, the contempt of court term is an action that can undermine the dignity of a judicial power. Oemar Seno Adjie argued that there are five categories of behavior that are classified as contempt of court, including behavior attacking the integrity and impartiality of the court (Scandalising the Court) and insulting justice through publication (Sub-Judice Rule). Both forms of contempt of court have the potential to be carried out by a press media. Law Number 40 of 1999 concerning the Press constructs two forms of punishment for the implementation of Law Number 40 of 1999 concerning the Press, namely imprisonment and fines. However, there is no further explanation regarding the legal liability of the press media if it is proven to be committing Scandalising the Court or Sub-Judice Rule. This research is a normative legal research by utilizing literature study as a technique for gathering legal materials. Therefore, the results of this study are a juridical study of the potential and contempt of court violations conducted by a press media in Indonesia and can be an academic research for further research related to contempt court normative arrangements in Indonesia.